Agents and artificial intelligence : 6th International Conference, ICAART 2014, Angers, France, March 6-8, 2014, Revised selected papers /: 6th International Conference, ICAART 2014, Angers, France, March 6-8, 2014, Revised selected papers. (2015) - Unknown
No abstract available